2020
DOI: 10.13106/jafeb.2020.vol7.no12.927
|View full text |Cite
|
Sign up to set email alerts
|

Internal Control Effectiveness and Business Survival: Evidence from Thai Food Businesses

Abstract: This study aims at investigating the effects of internal control effectiveness on business survival of food businesses in Thailand through the mediators of productivity improvement and value creation. In this study, 155 food businesses in Thailand are the samples of the study. The results show that internal control effectiveness has a significant influence on productivity improvement and business survival. Productivity improvement critically affects value creation and business survival while value creation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…For example, Hasan (2023) found that the more a company moves towards digital transformation the more it leads to adequacy and reliability of accounting information and thus benefits its users. This is consistent with Phornlaphatrachakorn and Kalasindhu (2021) who found that digital accounting has a significant effect on the usefulness of accounting information and the effectiveness of strategic decision. In addition, Johnston and Zhang (2018) found that investing in technology reduces reporting delay by automating the reporting process.…”
Section: Literature Reviewsupporting
confidence: 91%
See 4 more Smart Citations
“…For example, Hasan (2023) found that the more a company moves towards digital transformation the more it leads to adequacy and reliability of accounting information and thus benefits its users. This is consistent with Phornlaphatrachakorn and Kalasindhu (2021) who found that digital accounting has a significant effect on the usefulness of accounting information and the effectiveness of strategic decision. In addition, Johnston and Zhang (2018) found that investing in technology reduces reporting delay by automating the reporting process.…”
Section: Literature Reviewsupporting
confidence: 91%
“…Based on the results and discussions, it can be concluded that the use of technology improves the timeliness of financial reports, and makes publishing financial reports faster. These results are consistent with Johnston and Zhang (2018), Gulin, Hladika, and Valenta (2019), Aksoy, Yilmaz, Topcu, and Uysal (2021), Phornlaphatrachakorn and Kalasindhu (2021) and Hasan (2023) who found that the quality of accounting information affected by digital transformation. These results are also consistent with Johnston and Zhang (2018) who found that investing in technology reduces reporting delays by automating the reporting and closing process.…”
supporting
confidence: 90%
See 3 more Smart Citations